2021
DOI: 10.2106/jbjs.20.01714
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Morphology and Bronchial Narrowing Are Related to Pulmonary Function in Adolescent Idiopathic Scoliosis

Abstract: Background:In adolescent idiopathic scoliosis (AIS), lung function impairment is not necessarily related to the coronal spinal deformity. Recently, right-sided bronchial narrowing has been reported in thoracic AIS. The aim of this study was to describe the relation of chest and spinal deformity parameters, bronchial narrowing, and lung volumes with pulmonary function in preoperative AIS.Methods:Spinal radiographs, low-dose computed tomographic (CT) scans of the spine including the chest, and pulmonary function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…RHi and SPi were significantly improved after concave RR surgery with the outrigger. In fact, it has been reported that TK correlates with SPi, and RHi correlates with the main thoracic Cobb angle in patients with AIS [37]. Our data showed a 6 • difference between the two groups after surgery, although the difference may be difficult to prove to be clinically superior.…”
Section: Discussionmentioning
confidence: 48%
“…RHi and SPi were significantly improved after concave RR surgery with the outrigger. In fact, it has been reported that TK correlates with SPi, and RHi correlates with the main thoracic Cobb angle in patients with AIS [37]. Our data showed a 6 • difference between the two groups after surgery, although the difference may be difficult to prove to be clinically superior.…”
Section: Discussionmentioning
confidence: 48%
“…Farrell et al elegantly demonstrated that the pulmonary dysfunction in patients with adolescent idiopathic scoliosis is not only restrictive but also obstructive. Correlating low-dose computed tomographic (CT) scans with pulmonary function tests, the authors found that chest intrusion creates right-sided bronchial narrowing and lung function loss in preoperative patients with adolescent idiopathic scoliosis, with nearly half (48%) of patients having a percent-of-predicted forced expiratory volume in 1 second (FEV1%) or percent-of-predicted forced vital capacity (FVC%) that was <65% compared with controls 14 .…”
Section: Spinementioning
confidence: 99%
“…It is, however, more accurately characterized as a 3-dimensional (3D) deformity of the spine in the coronal, sagittal, and axial planes [1][2][3]. Due to the intrinsic rotation of the curvatures, significant deformation of the chest also occurs [4,5]. For primary thoracic curves, in the coronal plane, lateral bending is related to narrowing of the hemithorax on the convex side of the curve.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal intrusion ratio: This parameter represents the sagittal intrusion of the thoracic spine into the chest and has been demonstrated to be related to the size of the airways [5,23]. SIr is the ratio between the distance from the anterior vertebral column contour to the interior contour of the convex ribs and the distance from the internal sternal surface to the anterior contour of the vertebral column.…”
mentioning
confidence: 99%